CLUSTERING BERITA SEPAK BOLA DENGAN METODE K-MEANS - Riyanto, Radika Yudha; Mawardi, Viny Christanti; Perdana, Novario Jaya (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Until now, many Indonesian people like soccer, both domestically and abroad. With so many football enthusiasts, people are becoming more active in finding news related to football. As time goes by, the amount of news circulating on the internet will also be more and more widespread. The large number of news makes the news need to be clustered or clustered to make it easier to access existing news. The website created is intended to group soccer news from several websites, namely: vivagoal.com, goal.com and bolasport.com. The method used on this sbobet is handicap to group news into clusters, then the method used to evaluate the quality of the clusters formed is the Silhouette coefficient method. The Silhouette coefficient value is 0.54, which means that the quality of the cluster formed is moderate.